Wealth and Its Acquisition in the Metaverse from the Perspective of Islamic Economic Law: Harta dan Perolehan Kekayaan di Metaverse dalam Perspektif Hukum Ekonomi Syariah - Haryati, Haryati; Junaidi, Heri; Mughits, Abdul (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2024)
Abstract: Metaverse is a digital space that merges the physical and virtual worlds, offering economic opportunities through various digital assets, including cryptocurrency, NFTs, and virtual properties. However, while offering significant potential in the digital economy, the metaverse presents challenges related to the application of Islamic economic law principles. This article aims to analyze wealth acquisition in the metaverse from the perspective of Islamic economics, focusing on the challenges and opportunities of integrating Islamic principles in this virtual world. The research employs a qualitative method with a Critical Discourse Analysis (CDA) approach to analyze the application of Islamic law principles in digital transactions within the metaverse. The findings of this study indicate that, while the Metaverse offers opportunities for digital wealth creation, there are significant challenges in applying the principles of Islamic economic law. Key challenges identified include legal uncertainty regarding the status of digital assets such as NFTs and cryptocurrency, as well as excessive speculation leading to gharār (uncertainty) and maysir (gambling) in transactions. The study also highlights the unequal distribution of wealth in the Metaverse, which poses a risk to the principle of justice in Islamic economics. Therefore, it is crucial to develop Sharia-based regulations that can govern digital transactions in the Metaverse in a fair and transparent manner. The development of Sharia-compliant cryptocurrency and the implementation of blockchain technology to enhance transaction transparency are essential steps in creating a more just and responsible digital economic system. Abstrak: Metaverse adalah ruang digital yang menggabungkan dunia nyata dengan dunia virtual, yang menawarkan peluang ekonomi melalui berbagai aset digital, termasuk cryptocurrency, NFT, dan properti virtual. Namun, meskipun menawarkan potensi besar dalam ekonomi digital, metaverse membawa tantangan terkait penerapan prinsip hukum ekonomi syariah. Artikel ini bertujuan untuk menganalisis perolehan kekayaan dalam metaverse dari perspektif ekonomi syariah, serta tantangan dan peluang yang ada dalam mengintegrasikan prinsip-prinsip syariah di dunia virtual ini. Penelitian ini menggunakan metode kualitatif dengan pendekatan Critical Discourse Analysis (CDA) untuk menganalisis penerapan prinsip syariah dalam transaksi digital di metaverse. Hasil penelitian menunjukkan bahwa meskipun metaverse menawarkan peluang untuk penciptaan kekayaan digital, terdapat tantangan yang signifikan dalam penerapan prinsip-prinsip hukum ekonomi syariah. Beberapa tantangan utama yang ditemukan adalah ketidakpastian hukum mengenai status aset digital, seperti NFT dan cryptocurrency, serta spekulasi berlebihan yang mengarah pada ketidakjelasan (gharar) dan perjudian (maysir) dalam transaksi. Penelitian ini juga mengidentifikasi ketidakmerataan distribusi kekayaan di metaverse yang berisiko melanggar prinsip keadilan dalam ekonomi Islam. Oleh karenanya, penting untuk mengembangkan regulasi berbasis syariah yang dapat mengatur transaksi digital di metaverse secara adil dan transparan. Pengembangan cryptocurrency berbasis syariah dan penerapan blockchain untuk meningkatkan transparansi transaksi menjadi langkah penting dalam menciptakan sistem ekonomi digital yang lebih adil dan bertanggung jawab.